Implementasi Model Pembelajaran Berbasis Masalah dengan Teknik Klarifikasi Nilai Mata Pelajaran PPKn di SMA - Herningsih; Ihsan (Penerbit STKIP PGRI Bangkalan, 2020)
Research that aims to determine the implementation of problem-based learning model with values ​​clarification techniques on the learning PPKn of class X SMA.This study was a quantitative approach with the quasi experimental research methods.The study design was a randomized control group pretest posttest. The data were collected using cognitive test, observation, and questionnaire. Data were analyzed using t-test and analysis of variance (Anova)and gain score. The research finding that the application of problem based-learning use with values ​​clarification techniques in teaching civic is more effective on civic learning. It can be seen from the outcomes, that the significance level which is lower than 0.05 (p = 0.000 <0.05) and the gain score. The experimental class obtained the gain score of 0.57 which is in the